Belonging, social connection and non‐clinical care: Experiences of HIV peer support among recently diagnosed people living with HIV in Australia. (19th June 2022) - Wells, Nathanael; Philpot, Steven P.; Murphy, Dean; Ellard, Jeanne; Howard, Chris; Rule, John; Fairley, Christopher; Prestage, Garrett; ,
Abstract: Effective HIV treatments have transformed the medical needs of people living with HIV (PLHIV) to a chronic condition. However, stigma, poorer mental health outcomes and social isolation remain significant challenges for many PLHIV. HIV peer support programs have assisted PLHIV in navigating the clinical, emotional and social aspects of living with HIV. We draw on semi‐structured interviews with 26 recently diagnosed PLHIV in Australia to explore experiences of HIV peer support services. Our thematic analysis identified three overarching themes. First, participants commonly reported that peer support programs offered a sense of belonging and connection to a broader HIV community. This established a network, sometimes separate to their existing social networks, of other PLHIV with whom to share experiences of HIV. Second, peer‐based programs provided an opportunity for participants to hear firsthand, non‐clinical perspectives on living with HIV. While participants valued the clinical care they received, the perspectives of peers gave participants insights into how others had managed aspects of living with HIV such as disclosure, sex and relationships. Finally, participants highlighted important considerations around ensuring referrals were made to socially and culturally appropriate support programs. Peer support programs fill an important gap in HIV care, working alongside and extending the work of the clinical management of HIV. Incorporating formal referrals to peer support services as part of the HIV diagnosis process could assist recently diagnosed PLHIV in adjusting to a positive diagnosis.